La inmigración portuguesa en las cuencas mineras de León - Martínez Álvarez, O.; Reyes Herrero, Rosa María; Rodríguez Sánchez, María del Carmen (Estudios humanísticos. Geografía, historia y arte, 1988)
The immigration from the North-East of Portugal to the mining areas in León and Asturias starts in the early 60s. This movement will make up for the Spanish emigration to other industrial regions, looking for working improvemt. The peculiar characteristic of the Portuguese immigration is its secrecy because of tow main reasons: first of all, it was the Salazar Government who obstruct the emigration of young men before having served in the army. Later on, the Spanish authorities put obstacles to these immigrants. Nowadays, this group is still very important because of its large number and its social and economic implication in the province of León. At the same time, their situation has changed as they have achieved greater consideration from the oficial organisms of the Spanish and Portuguese governments.